IDENTIFICATION OF LACTIC ACID BACTERIA FROM BIOFLOK TECHNOLOGY WHICH HAS BEEN GAVE MOLLASES ON RED TILAPIA (Oreochromis sp.) AQUACULTURE - Nelli Karolina Sitorus; Iesje Lukistyowati; Henni Syawal; Iskandar Putra (Berkala Perikanan Terubuk, 2019)
The aim of this research was to  determine the types of lactic acid bacteria from biofloc technology with the addition of mollase in red tilapia aquaculture containers and to determine the optimum growth of lactic acid bacteria at pH 2, 4, and 6, and also to observe the density of bacteria in the biofloc container water during maintenance. The methods used in this research are survey and experiments by taking flok from maintenance container and then identifying the lactic acid bacteria. The results of lactic acid bacteria inoculation obtained 16 isolates isolated from floc which can only grow at pH 4 and pH 6. Identification based on physical tests, chemical tests, and biochemical tests showed that the isolates were classified into Bacillus and Streptococcus. The amount of bacterial density water from containers of biofloc technology were given mollase during research reached the highest point in the third week, which averaged 109 CFU/mL.